ChemInform Abstract: Chiral Phosphoric Acid Directed Regioselective Acetalization of Carbohydrate‐Derived 1, 2‐Diols. Issue 19 (13th May 2014) - Mensah, Enoch; Camasso, Nicole; Kaplan, Will; Nagorny, Pavel
Abstract The first example of a chiral‐catalyst‐controlled regioselective acetalization of C2/C3‐OH carbohydrates such as (I) and (VIII) is described.